2009
DOI: 10.1158/0008-5472.can-08-2661
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Diffusion Tensor Magnetic Resonance Imaging Study of Radiation-Induced White Matter Damage in a Rat Model

Abstract: Radiation-induced white matter (WM) damage is a major side effect of whole brain irradiation among childhood cancer survivors. We evaluate longitudinally the diffusion characteristics of the late radiation-induced WM damage in a rat model after 25 and 30 Gy irradiation to the hemibrain at 8 time points from 2 to 48 weeks postradiation. We hypothesize that diffusion tensor magnetic resonance imaging (DTI) indices including fractional anisotropy (FA), trace, axial diffusivity (L // ), and radial diffusivity (L ?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 35 publications
(52 reference statements)
9
100
1
4
Order By: Relevance
“…32,33 In the posterior part of the cingulum, the means of the RD were increased by 11.4% at the end of RT (p < 0.001) and by 10.5% 1-month post-RT from pre-RT (p < 0.008), while the means in the AD were not changed significantly at both time points, suggesting the radiationinduced demyelination is predominant. Similarly, in the fornix, the means of the RD were increased by 7.1% at the end II.…”
Section: Iiic1 Longitudinal Percentage Changes In Diffusion Indicesmentioning
confidence: 98%
“…32,33 In the posterior part of the cingulum, the means of the RD were increased by 11.4% at the end of RT (p < 0.001) and by 10.5% 1-month post-RT from pre-RT (p < 0.008), while the means in the AD were not changed significantly at both time points, suggesting the radiationinduced demyelination is predominant. Similarly, in the fornix, the means of the RD were increased by 7.1% at the end II.…”
Section: Iiic1 Longitudinal Percentage Changes In Diffusion Indicesmentioning
confidence: 98%
“…Decreased FA is common in white matter injury, typically attributed to its association with an increased radial diffusivity (λr); this is observed in periventricular white matter in hydrocephalus, posterior reversible encephalopathy syndrome, peritumoral edema (10), and mitochondrial disease (13). A few disease states are reported in which a decreased FA is associated with decreased axial diffusivity (λa), including radiation injury (21). However, we identified few disease states reported with an increased axial diffusivity, the pattern we observed in this study.…”
Section: Pediatric Diabetic Ketoacidosismentioning
confidence: 99%
“…It is commonly used to evaluate the WM in rodent models. 4,19,20 2) It has been reported that the EC is a major WM damage region in the mild-HI-injury neonatal rat model, 4,18 whereas mild HI insult produces a relative sparing injury of GM. …”
Section: Image Analysismentioning
confidence: 99%